2014
DOI: 10.1016/j.jenvman.2014.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Keeping agricultural soil out of rivers: Evidence of sediment and nutrient accumulation within field wetlands in the UK

Abstract: Intensification of agriculture has resulted in increased soil degradation and erosion, with associated pollution of surface waters. Small field wetlands, constructed along runoff pathways, offer one option for slowing down and storing runoff in order to allow more time for sedimentation and for nutrients to be taken up by plants or micro-organisms. This paper describes research to provide quantitative evidence for the effectiveness of small field wetlands in the UK landscape. Ten wetlands were built on four fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 23 publications
5
42
0
1
Order By: Relevance
“…Others have suggested smaller, strategically placed features could play a key role (Braskerud et al ., 2005; Ockenden et al ., 2014). However, such work commonly focuses on anthropogenic features with associated construction and maintenance costs (Ockenden et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Others have suggested smaller, strategically placed features could play a key role (Braskerud et al ., 2005; Ockenden et al ., 2014). However, such work commonly focuses on anthropogenic features with associated construction and maintenance costs (Ockenden et al ., 2012).…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, undesirable inflows into the ecosystem, caused by anthropogenic activity, can shake this harmony and degrade living conditions [1]. Human influence on the environment is increasing due to mass production of technological goods [2], intensification of agriculture [3], the rapid rate of urbanization, and growing demand of fossil fuels for energy and transport [4]. According to data from the International Energy Agency, between 1971-2014, global primary energy consumption has increased by 2.5 times, as from 5.5 GTOE in 1971 to 13.7 GTOE for 2014 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that in runoff from agricultural fields, phosphorus is transported largely as particulate phosphorus [15][16][17][19][20][21][22]. Therefore, sedimentation is likely to be the predominant phosphorus removal process in wetlands receiving high phosphorus loads [23][24][25][26][27]. In addition to estimations of nutrient removal in individual wetlands based on water monitoring data, measurements of particulate phosphorus accumulation on sediments [23] were therefore included here.…”
Section: Introductionmentioning
confidence: 99%